Tonsil-derived mesenchymal stem cells alleviate skin inflammation by modulating neutrophil extracellular trap formation and T cell migration - Hyun Ju Kim; Kyung-Ah Cho; So-Youn Woo (PLoS ONE, 2026)
Skin inflammation arises from complex interactions among immune cells, particularly T cells and neutrophils. Mesenchymal stem cells (MSCs) exhibit potent immunomodulatory properties, but the specific roles of tonsil-derived MSCs (T-MSCs) in regulating neutrophil extracellular trap (NET) formation and cell death, as well as T cell migration in inflammatory skin conditions, remain poorly defined. In this study, the therapeutic effects and mechanisms of T-MSCs were investigated in a 2,4-dinitrochlorobenzene (DNCB)-induced skin inflammation model, with a focus on NET formation and T cell migration. T-MSCs were intravenously administered to mice with DNCB-induced skin inflammation; inflammation severity and immune cell dynamics were evaluated using histological analysis, flow cytometry, immunostaining, microarray profiling, NET assays, and T cell migration assays. T-MSC treatment reduced DNCB-induced skin inflammation, as demonstrated by decreased epidermal thickness and neutrophil infiltration. Although T-MSCs enhanced NET formation in vitro , they suppressed neutrophil accumulation in vivo . T-MSCs also modulated the distribution and activation of T cell subsets in the skin and secondary lymphoid organs. Gene expression profiling revealed that T-MSCs regulated pathways associated with inflammation and neutrophil activity, including those involved in immune cell trafficking and NET formation. Moreover, T-MSCs promoted T cell migration, although this effect was influenced by neutrophil presence, indicating complex interplay among immune cells. These findings demonstrate that T-MSCs exert anti-inflammatory effects in DNCB-induced skin inflammation by modulating NET formation and T cell migration, revealing a novel immunoregulatory mechanism and supporting their therapeutic potential for inflammatory skin diseases.